2022
DOI: 10.3389/fnmol.2022.844194
|View full text |Cite
|
Sign up to set email alerts
|

Role of Extracellular Vesicles in Glia-Neuron Intercellular Communication

Abstract: Cross talk between glia and neurons is crucial for a variety of biological functions, ranging from nervous system development, axonal conduction, synaptic transmission, neural circuit maturation, to homeostasis maintenance. Extracellular vesicles (EVs), which were initially described as cellular debris and were devoid of biological function, are now recognized as key components in cell-cell communication and play a critical role in glia-neuron communication. EVs transport the proteins, lipids, and nucleic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 158 publications
(178 reference statements)
0
13
0
Order By: Relevance
“…EVs have been shown to participate in the communication between glial cells and neuronal cells, and it is believed that EVs may change the morphology and function of target cells when transmitting information, regulating homeostasis, immune function and inter-glia communication. It plays a key role in the transfer of biomolecules [ 22 ]. However, as a carrier that can target systemic organs, the functions of EVs are complex and diverse, and there are also potential harmful effects.…”
Section: Evs In Health and Diseasementioning
confidence: 99%
“…EVs have been shown to participate in the communication between glial cells and neuronal cells, and it is believed that EVs may change the morphology and function of target cells when transmitting information, regulating homeostasis, immune function and inter-glia communication. It plays a key role in the transfer of biomolecules [ 22 ]. However, as a carrier that can target systemic organs, the functions of EVs are complex and diverse, and there are also potential harmful effects.…”
Section: Evs In Health and Diseasementioning
confidence: 99%
“…Moreover, it has been found that oligodendrocytes of the central nervous system (CNS), as well as Schwann cells (SCs) of the peripheral nervous system (PNS), can even transfer ribosomes to neuronal axons [ 290 , 291 ]. Given this ability of SCs, as well as of oligodendrocytes, to release EVs that allow the lateral transfer of molecules to axons [ 292 , 293 , 294 ], it can be suggested that EVs are also involved in the transport to axons of ribosomes, which can then allow the local translation of pre-localized mRNAs, in response to specific extracellular signals.…”
Section: Role Of Rbps In Rna Sorting To Extracellular Vesiclesmentioning
confidence: 99%
“…10 In the central nervous system (CNS), exosomes can regulate intercellular communication between glial cells and neurons to modulate neuroplasticity. 11,12 A recent study showed that exosomes secreted by microglia can upregulate and deliver mi-croRNAs (miRNAs) to inhibit neurogenesis in the hippocampal dentate gyrus (DG), consequently exacerbating depressive-like behaviors in rats subjected to chronic unpredictable mild stress (CUMS). 13 Recent studies have highlighted a pivotal role for oligodendrocytes in the pathobiology of depression, given their critical functions in myelin sheath formation, support of axonal energy metabolism, and regulation of various neuroplasticity processes.…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes are small, double‐membraned vesicles that envelope various biomolecular cargoes 10 . In the central nervous system (CNS), exosomes can regulate intercellular communication between glial cells and neurons to modulate neuroplasticity 11,12 . A recent study showed that exosomes secreted by microglia can upregulate and deliver microRNAs (miRNAs) to inhibit neurogenesis in the hippocampal dentate gyrus (DG), consequently exacerbating depressive‐like behaviors in rats subjected to chronic unpredictable mild stress (CUMS) 13 …”
Section: Introductionmentioning
confidence: 99%